Diversity and abundance of antibiotic resistance of bacteria during the seedling period in marine fish cage-culture areas of Hainan, China. (April 2019) - Wu, Jinjun; Mao, Can; Deng, Yiqin; Guo, Zhixun; Liu, Guangfeng; Xu, Liwen; Bei, Lei; Su, Youlu; Feng, Juan
Abstract: Antibiotic resistance has become an important focus of research in the aquaculture environment. However, few studies have evaluated antibiotic resistance during the seedling period in marine fish cage-culture areas. In this study, culture-dependent methods and quantitative polymerase chain reaction were used to identify and detect cultivable heterotrophic antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs), respectively, during the seedling period in a marine fish cage-culture areas of Hainan, China. Bacterial resistance to amoxicillin, erythromycin, and gentamicin was generally high (average on 27.67%, 23.61% and 37.32%, respectively), whereas resistance to furazolidone and nitrofurantoin was generally low (average on 0.14% and 7.425%). Alteromonas (32.72%) and Vibrio (24.77%) were the dominant genus of ARB. Most ARB were opportunistic pathogens, belonging to the phylum Proteobacteria (96.02%). The abundance of sul family genes was higher than that of tet family genes. Overall, the abundance of ARGs and the resistance rates in HW was highest. Highlights: Bacterial resistance to amoxicillin, erythromycin and gentamicin was generally high. Most antibiotic-resistant bacteria (ARB) strains were opportunistic pathogens. Alteromonas was the most dominant genus of ARB. The relative abundance of sul family genes was higher than that of tet family genes.